Tax-price elasticity of charitable donations: Evidence from the German taxpayer panel - Maja Adena (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2014)
I estimate permanent and transitory tax-price and income elasticity of charitable giving in Germany using a rich panel data of tax return for the years 2001-2006. Income tax reforms were implemented in 2004 and 2005. The results suggest that the permanent tax-price elasticity varies significantly by income class, ranging from -0.2 for low incomes to -1.6 for higher incomes. Permanent income elasticity does not vary much among income classes, is rather low, and ranges between 0.2-0.3. The donors adjust their donations gradually after changes in the tax schedule and respond to future predictable changes in price. They respond to changes in current and, to a smaller extent, in future income. – – In dieser Studie wurde die permanente und transitorische Steuerpreis- und Einkommenselastizität der Spenden in Deutschland geschätzt. Basis für die Schätzung ist das umfangreiche Taxpayer-Panel, welches alle Steuermerkmale der Steuerzahler in Deutschland für die Jahre 2001-2006 erfasst. Die Ergebnisse suggerieren, dass die permanente Steuerpreiselastizität, je nach Einkommensklasse, sich stark unterscheidet; sie reicht von -0.2 für niedrige Einkommen bis -1.6 für höhere Einkommen. Dahingegen ist die permanente Einkommenselastizität für unterschiedliche Einkommensklassen ähnlich; insgesamt ist sie sehr niedrig und liegt zwischen 0.2 und 0.3. Spender passen ihre Spendenentscheidung nach Steueränderungen verzögert an, sie reagieren auch auf zukünftige vorausschaubare Preisänderungen. Sie reagieren auf aktuelle und weniger auf zukünftige Änderungen des Einkommens.
Keywords: H24; H31; D12; 330; charitable giving; price elasticity; tax incentives